Polymer-assisted spinodal decomposition enabling a three-dimensional interconnected porous Na3.4Fe2.4(PO4)1.4P2O7@C material for enhanced sodium-ion batteries - Nian Yang; Ruiyuan Tian; Fei Du (Discover Electrochemistry)
Abstract Na4Fe3(PO4)2P2O7 (NFPP), an Iron-based mixed polyanion phosphate, is regarded as a potential cathode material for sodium-ion batteries. However, the application is often constrained by the inherently sluggish Na+ diffusion and low electronic conductivity. Herein, we synthesized a 3D interconnected porous structural pure-phase nonstoichiometric Na3.4Fe2.4(PO4)1.4P2O7/carbon composite (3DP-NFPP@C). This was achieved through a straightforward polymer-assisted spinodal decomposition strategy, facilitated by the controlled evaporation of selective solvents during phase separation. As the interconnected porous structures provide fast ion diffusion channels, and the carbon coating enables enhanced electronic conductivity, the 3DP-NFPP@C composite exhibits an exceptional rate capability of 62.8 mAh g−1 at 100 C, nearly doubling the performance of the non-porous counterpart N-NFPP@C, which delivers 32.9 mAh g⁻1. Furthermore, it demonstrates a prolonged cycling life exceeding 8000 cycles, with a capacity retention of 91.5%. These findings offer valuable insights into the development of advanced cathode materials for high-performance sodium-ion batteries.